The world's youth adolescence in eight regions of the globe - Brown, B. Bradford 1949-; Larson, Reed 1950-; Saraswati, T. S. (Cambridge University Press, 2002)
The life stage of adolescence now occurs in most corners of the world, but it takes different forms in different regions. Peers, with such a central role in Western adolescence, play a comparatively minor role in the lives of Arabic and South Asian adolescents. Emotional turmoil and individuation from family occur in some societies but not others. Adolescent sexual revolutions are sweeping through Japan and Latin America. In this 2002 book, scholars from eight regions of the world describe the distinct nature of adolescence in their regions. They draw on research to address standard topics regarding this age - family and peer relationships, schooling, preparation for work, physical and mental health - and show how these have a different cast across societies. As a whole, the book depicts how rapid global change is dramatically altering the experience of the adolescent transition, creating opportunities and challenges for adolescents, parents, teachers, and concerned others